2019
DOI: 10.1172/jci129388
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ARPC1B impairs cytotoxic T lymphocyte maintenance and cytolytic activity

Abstract: CD8 cytotoxic T lymphocytes (CTLs) rely on rapid reorganization of the branched F-actin network to drive the polarized secretion of lytic granules, initiating target cell death during the adaptive immune response. Branched F-actin is generated by the nucleation factor actin-related protein 2/3 (Arp2/3) complex. Patients with mutations in the actin-related protein complex 1B (ARPC1B) subunit of Arp2/3 show combined immunodeficiency, with symptoms of immune dysregulation, including recurrent viral infections and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 81 publications
4
77
0
Order By: Relevance
“…Loss-of-function mutations of ARPC1B give rise to multisystem inflammatory and immunodeficiency diseases (Brigida et al, 2018;Kahr et al, 2017;Kuijpers et al, 2017;Randzavola et al, 2019;Somech et al, 2017;Volpi et al, 2019), similar to Wiskott-Aldrich syndrome that is caused by mutations in the Arp2/3 activator WASP (Bosticardo et al, 2009). While some patients carry mutations causing premature protein termination and total loss of ARPC1B protein, four point mutations -W104S, A105V, V208F and A238T have also been observed in patients (Brigida et al, 2018;Kahr et al, 2017;Volpi et al, 2019) (Fig.…”
Section: Isoform Specific Subunit Conformation and Determinants Of Acmentioning
confidence: 98%
See 1 more Smart Citation
“…Loss-of-function mutations of ARPC1B give rise to multisystem inflammatory and immunodeficiency diseases (Brigida et al, 2018;Kahr et al, 2017;Kuijpers et al, 2017;Randzavola et al, 2019;Somech et al, 2017;Volpi et al, 2019), similar to Wiskott-Aldrich syndrome that is caused by mutations in the Arp2/3 activator WASP (Bosticardo et al, 2009). While some patients carry mutations causing premature protein termination and total loss of ARPC1B protein, four point mutations -W104S, A105V, V208F and A238T have also been observed in patients (Brigida et al, 2018;Kahr et al, 2017;Volpi et al, 2019) (Fig.…”
Section: Isoform Specific Subunit Conformation and Determinants Of Acmentioning
confidence: 98%
“…Recent work has shown that the ARPC1 and ARPC5 isoforms differentially affect the actin nucleating properties of the Arp2/3 complex and the stability of the branched filament networks it generates (Abella et al, 2016). Furthermore, tissue-specific expression patterns of subunit isoforms, together with isoform-specific susceptibility to disease-causing point mutations, point to distinct physiological roles for particular Arp2/3 isoforms in nuclei positioning in skeletal muscle (Roman et al, 2017), as well as cytotoxic T lymphocyte maintenance and activity (Brigida et al, 2018;Kuijpers et al, 2017;Randzavola et al, 2019;Somech et al, 2017;Volpi et al, 2019;Roman et al, 2017;Kahr et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we identified the ARP2/3 complex subunit ARPC1B ( Supplementary table 3) to be oxidized at its residues Cys342 and Cys346. ARPC1B expression is restricted to hematopoietic cells and germline mutations of ARPC1B recently were demonstrated to affect T cells causing immunodeficiency (131,132). Data of our study suggest mtROS as a mechanistic link between how T cells involve the ARP2/3 complex in activation and implicate Cys342 and Cys346 of ARPC1B (+2%) as novel H2O2 sensitive thiols which may potentially mediate interactions with several candidate proteins, including Cytoplasmic FMR1-interacting protein 2 (CYFIP2, Supplementary table 3) that was found oxidized at positions Cys1087 and Cys1088 (+7%).…”
Section: Fine-tuning Mtros Along Metabolic Reprogramming Of T Cellsmentioning
confidence: 99%
“…Loss-of-function mutations of ARPC1B give rise to multisystem inflammatory and immunodeficiency diseases (Brigida et al, 2018;Kahr et al, 2017;Kuijpers et al, 2017;Randzavola et al, 2019;Somech et al, 2017;Volpi et al, 2019), similar to Wiskott-Aldrich syndrome that is caused by mutations in the Arp2/3 activator WASP (Bosticardo et al, 2009). While some patients carry mutations causing premature protein termination and total loss of ARPC1B protein, four point mutations -W104S, A105V, V208F and A238T -have also been observed in patients (Brigida et al, 2018;Kahr et al, 2017;Volpi et al, 2019) (Figure 2A, right, purple spheres).…”
Section: Isoform Specific Subunit Conformation and Determinants Of Acmentioning
confidence: 97%
“…Recent work has shown that the ARPC1 and ARPC5 isoforms differentially affect the actin nucleating properties of the Arp2/3 complex and the stability of the branched filament networks it generates (Abella et al, 2016). Furthermore, tissue-specific expression patterns of subunit isoforms, together with isoformspecific susceptibility to disease-causing point mutations, point to distinct physiological roles for particular Arp2/3 isoforms including cytotoxic T lymphocyte maintenance and activity (Brigida et al, 2018;Kahr et al, 2017;Kuijpers et al, 2017;Randzavola et al, 2019;Roman et al, 2017;Somech et al, 2017;Volpi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%